VISUALIZATION OF STRESS FIELDS IN MONOCRYSTALS BY THE JOINT APPLICATION OF X-RAY PENDELLOSUNG FRINGES AND MOIR PATTERNS METHODS - Aloumyan, K. V.; Eyramjyan, T. H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2005)
In the paper the results of visualization of the isostrain lines for local regions of dislocation Si monocrystals by joint application of X-ray Moire and Pendellosung Fringes methods are presented.